A new fully liquid presentation of MenACWY-CRM conjugate vaccine: Results from a multicentre, randomised, controlled, observer-blind study. Issue 45 (29th October 2021) - Vandermeulen, Corinne; Leroux-Roels, Isabel; Vandeleur, James; Staniscia, Tommaso; Girard, Ginette; Ferguson, Murdo; Icardi, Giancarlo; Schwarz, Tino F; Neville, A Munro; Nolan, Terry; Cinquetti, Sandro; Akhund, Tauseefullah; et al.
Highlights: A new fully liquid version of the MenACWY-CRM conjugate vaccine has been developed. The serogroup A component was modified from lyophilised to liquid presentation. Liquid vaccine was non-inferior to licensed vaccine in immune response against MenA. Immune responses against other serogroups were similar with both presentations. The reactogenicity and safety profiles of the vaccine presentations were similar. Abstract: Background: The currently licensed quadrivalent MenACWY-CRM conjugate vaccine presentation consists of two vials (lyophilised MenA and liquid MenCWY) to be reconstituted before injection. A new fully liquid formulation in a single vial has been developed to further improve the vaccine presentation. Since the MenA structure is subject to hydrolytic degradation, this study was conducted to compare the immunogenicity and safety of the investigational MenACWY-CRM liquid vaccine with the licensed vaccine. Methods: In this multicentre, randomised, controlled, observer-blind, phase 2b study, 979 healthy adults were administered a single dose of MenACWY-CRM liquid presentation or the currently licensed MenACWY-CRM vaccine. MenA free saccharide generation was accelerated to approximately 30% in the liquid presentation and MenA polysaccharide O-acetylation was reduced to approximately 40%, according to a controlled procedure. Immunological non-inferiority of the MenACWY-CRM liquid to the licensed vaccine, as measured by human serum bactericidal assay (hSBA) geometric mean titres (GMTs) against MenA 1 month post-vaccination, was the primary study objective. Safety assessment was among the secondary objectives. Results: Immune responses against each serogroup were similar between the two vaccine groups and was non-inferior for MenA. Adjusted hSBA GMTs for MenA were 185.16 and 211.33 for the MenACWY-CRM liquid presentation and currently licensed vaccine presentation, respectively. The between-group ratio of hSBA GMTs for MenA was 0.88, with a two-sided 95% confidence interval lower limit of 0.64, greater than the prespecified non-inferiority margin of 0.5, thus meeting the primary study objective. Both vaccines were well tolerated. No serious adverse events were considered related to vaccination. Conclusions: The levels of MenA free saccharide and polysaccharide O-acetylation did not affect the immunogenicity of the fully liquid presentation, which was demonstrated to be non-inferior to the immunogenicity of the currently licensed MenACWY-CRM vaccine against MenA. The immunogenicity, reactogenicity and safety profiles of the two vaccine presentations were similar.